Desenvolvimento de uma bebida fermentada à base de xerém de castanha de caju (Anacardium occidentale L.) - Nascimento, Rita Sannara Bandeira do (2024)
Consumer interest in functional foods has grown in recent years. Plant-based milk alternatives (PBMA) are also in clear demand, influenced by factors such as lactose intolerance, allergies, veganism, environmental sustainability, and ethical considerations. Recognizing the relevance of cashew nut kernels in Brazilian commerce and the by-products generated during its production due to breakages and irregularities, this study proposed utilizing cashew nut by- product in the preparation of a plant-based beverage fermented with potentially probiotic bacteria. Cashew nut is considered an excellent source of lipids, proteins and carbohydrates. Therefore, this work aimed to develop and evaluate the functional potential of a cashew nut-based beverage fermented by the Lacticaseibacillus casei NRRL B-442 strain. The fermented beverage was prepared and its stability was evaluated over 42 days of refrigerated storage (4 °C), monitoring parameters such as pH, viability and concentration of lactic acid and sugars. Additionally, the survival rate of viable cells after simulated gastrointestinal digestion was quantified. A new fermentation was prepared and the fermented beverage was divided into two parts, which were added with sucrose (7%, w/v) or sucralose (0.2%, v/v) and were subjected to sensory analysis, including word association, hedonic scale, and CATA tests. During fermentation, the potentially probiotic microorganism demonstrated a preference for consuming glucose, resulting in the production of lactic acid. The fermented beverage was stable throughout refrigerated storage, with final viable cell counts greater than 12 log CFU/mL in all samples analyzed. During this period, the samples underwent post-acidification during storage, with lactic acid values above 9 g/L at the end of this period. After in vitro digestion on the 1st, 21st and 42nd days of storage, microorganism survival rates of 73.18% (9.55 log CFU/mL), 76.39% (10.68 log CFU/mL) and 75.06% (9.18 log CFU/mL) were observed, respectively. The products prepared were well accepted sensorially, with no significant difference between the samples sweetened with sucrose and sucralose, according to the tests applied. Overall, the results suggest that the cashew nut-based matrix is a promising alternative for the development of probiotic plant-based products. The development of this project made it possible to elaborate a fermented plant-based beverage with strong functional potential, providing a new product option for interested consumers.